Sequential adsorption-electrophoresis: combined procedure for purification of calcium-dependent cyclic nucleotide phosphodiesterase. - Kincaid, R L (1979)
A procedure for combined sequential affinity adsorption-electrophoresis has been devised. Its use for the rapid purification of a calcium-dependent cyclic nucleotide phosphodiesterase from bovine brain in high yield is described. In this procedure, proteins bound to a solid phase of calcium-dependent regulatory protein (CDR) linked to Sepharose 4B were electrophoretically eluted, concentrated, and separated, thus avoiding the large losses in activity incurred during attempts to purify further the phosphodiesterase eluted by conventional means. The highly purified phosphodiesterase prepared by this method was stable for months at -60 degrees C in the presence of glycerol. It has a higher affinity for cyclic GMP than for cyclic AMP, and hydrolysis of both substrates is stimulated 5- to 6-fold by calcium plus CDR. Factors that influence adsorption of the enzyme to CDR-Sepharose and selection of optimal conditions for electrophoresis were investigated. Sequential adsorption-electrophoresis should be generally useful in the purification of macromolecules for which affinity adsorbents are available. The procedures described here could be directly applicable to the purification of proteins that, like the phosphodiesterase, interact with CDR.